2012
DOI: 10.1016/j.jcrs.2012.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure measurements during flap preparation using 2 femtosecond lasers and 1 microkeratome in human donor eyes

Abstract: Dr. Sekundo is a member of the Scientific Advisory Board of Carl Zeiss Meditec AG, Jena, Germany. No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
(33 reference statements)
0
15
1
1
Order By: Relevance
“…Several in-vivo and in-vitro studies showed that IOP value would dramatically increase during femtosecond laser assisted corneal refractive surgeries as the response to attachment and suction. [15][16] In this study we did not detect a significant increase in IOP after lenticule creation, implying that the IOP rise might be temporary. And the SMILE procedure is safe.…”
Section: Discussioncontrasting
confidence: 50%
“…Several in-vivo and in-vitro studies showed that IOP value would dramatically increase during femtosecond laser assisted corneal refractive surgeries as the response to attachment and suction. [15][16] In this study we did not detect a significant increase in IOP after lenticule creation, implying that the IOP rise might be temporary. And the SMILE procedure is safe.…”
Section: Discussioncontrasting
confidence: 50%
“…These machines have been shown to elevate the IOP to a lower extent than traditional mechanical microkeratomes (MMKs); however, the “suction ON” to “suction OFF” time is considerably higher 2. Vetter et al3 showed IOP elevation up to 150 mmHg with flat corneal applanation interfaces and up to 65 mmHg with curved corneal interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the excimer laser digs from the surface a trench into the cornea while its energy is gradually absorbed [ 1 ]. On the other hand, the femtosecond laser creates cavitation bubbles at different depths of the cornea and thus an incision can be obtained faster [ 22 ]. We intended a complete perforation of the cornea during FLAK.…”
Section: Discussionmentioning
confidence: 99%